En villkorad gemenskap Hbtq, sexualitet och kristen frikyrklighet - carlström, charlotta (Kriterium, 2023)
Homosexuality, bisexuality, transgender and queer have long been a sensitive topic in Christian churches. As society has changed, some denominations have become increasingly affirming, while others see the changes as incompatible with Christian values. A Conditional Community is based on in-depth interviews with 29 lgbtq Christians and is the first Swedish scientific study on the subject. Using a phenomenological approach, the author investigate how sexuality, intimacy and faith are experienced by the interviewees and how their Christian identity interacts with their identity as lgbtq people. A Conditional Community is aimed at teachers, researchers and students in fields such as religious studies, sexology, gender studies and psychology. The book is also of interest to professionals who require knowledge on the subject, such as pastors and therapists. Furthermore, it can serve as a basis for discussions and reflection on faith, sexuality and lgbtq in the Free Church contexts.